The Surge Of Domestic Violence In India During Covid19-The Shadow Pandemic - Jyoti Singh,; Dr. Venkat Ram Reddy Minampati, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Domestic violence against women is a worldwide epidemic that harms all nations. Nationwide, the current COVID-19 epidemic and the associated lockdown period have seen a significant surge in domestic violence. If a shadow epidemic goes unchecked, it will destroy civilization, and we won't even be able to assess the true economic and social costs. Any violence that is happening within the 4 walls of the house like in marriage or live-in relationships is called Domestic Violence. It is abuse done by family members. Most of the research says that intimate partners mostly do it. It could also be between same-sex relationships or Heterosexual relationships. The scope of domestic violence includes psychological abuse, physical abuse, emotional abuse, sexual abuse, religious abuse, financial abuse, etc. Domestic homicide is also included in domestic violence like burning the bride, Honor killing, etc. In its broadest meaning, domestic violence might encompass hostility toward children, teenagers, or adults. The paper will outline this issue with the help of quantitative research and with the help of different authors' viewpoints. The objectives are mentioned so that the surge regarding this issue can be Determined. This study aims to look at the frequency and changes in domestic violence cases before and after the Coronavirus epidemic. A comparison of the two time periods is also carried out to see if there is any link between COVID-19-relatedlockdowns and recorded domestic violence instances.